DIGITISATION’S IMPACT ON ISLAMIC FINANCIAL INSTITUTIONS: WEBSITE-BASED FINANCING SYSTEM SERVICES - Fourika Dela Putriana; Budi Sukardi; Fuad Dhiya Ul Husaen (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2022)
This study will examine the effect of efficiency, reliability, privacy, fulfilment, responsiveness, and compliance on members' interest in applying for website-based financing products at BMT Amanah Ummah (AUM) Sukoharjo Central Java, Indonesia. This research is quantitative; the data come from a questionnaire distributed to all sharia financing customers at BMT AUM, and the data is analysed using multiple regression statistical techniques. The study's results prove that efficiency positively and significantly affects members' interest in submitting website-based online financing products at the BMT AUM. Reliability, privacy, and fulfilment do not affect members' interest in applying for a website-based online financing product at BMT AUM. Responsiveness has a positive but insignificant effect on members' interest in applying for website-based online financing products at BMT AUM. Compliance positively and significantly affects members' interest in applying for website-based online financing products at BMT AUM.